Contractor's application for an extension of time - Danial, Norhana (2007)
Invariably an evaluation of extension of time (EOT) will be made based on the information submitted by the contractor such as work programme and architect's instructions. Lack of information of delay is one of the common mistakes by the contractor in the application of EOT and this can lead to obstacles in prompt settlement of claims for EOT. The objectives of this research are: to identify the information that needs to be considered in evaluating extension of time application; to identify the common mistakes by the contractor in the application of extension of time; and to identify the ways to reduce the mistakes by the contractor in the application of extension of time. The methodology of this study includes literature reviews, data collection and analysis. Data is gathered from responses of questionnaire survey with professionals involved in the construction project. The research findings indicate that insufficient quality of information and poor presentation of the application to show how the progress of the work has been delayed remained as the highest common mistakes. This research highlights the ways to reduce the mistakes to speed up the evaluation process in order to establish the contractor's entitlement for EOT and also to avoid disputes about contractor's entitlement for EOT. In conclusion, the mistakes could be best controlled or reduced by the implementation of a document management system.